ANALISIS KEUNTUNGAN USAHA PUPUK ORGANIK DI PERUSAHAN CV. ARGONIAGA MANDIRI KECAMATAN BINTAUNA - Lantapa, Rivaldi; Manese, M. A.V; Wantasen, E.; Oroh, F. N.S (Universitas Sam Ratulangi, 2015)
PROFIT ANALYSIS OF ORGANIC FERTILIZER BUSINESS IN CV AGRONIAGA MANDIRI SUB-DISTRICT BINTAUNA. The purpose of this study was to determine the company profits per year. This research was done at CV Agroniaga Mandiri as the only company that produces organic fertilizer in the Bintauna Sub-district, North Bolaang Mongondow Regency. Â Data collected consist of primary data and secondary data. The primary data were collected by interview with questions list or quetionnaire, while secondary data were obtained from government Â agency that related with this research such as Department of Agriculture and Animal Husbandry of North Bolaang Mongondow. Data were analyzed with profit function method. The results showed that the total cost of production, revenue and profit of organic fertilizer business that obtained by CV Agroniaga Mandiri sequentially Rp. 259, 294,100 / year, Rp.405,000,000/year and Rp.145,705,900/year. Key words: Profit, organic fertilizer